A Novel In Vitro CypD-Mediated p53 Aggregation Assay Suggests a Model for Mitochondrial Permeability Transition by Chaperone Systems. Issue 20 (9th October 2016) - Lebedev, Ivan; Nemajerova, Alice; Foda, Zachariah H.; Kornaj, Maja; Tong, Michael; Moll, Ute M.; Seeliger, Markus A.
Abstract: Tissue necrosis as a consequence of ischemia–reperfusion injury and oxidative damage is a leading cause of permanent disability and death worldwide. The complete mechanism by which cells undergo necrosis upon oxidative stress is not understood. In response to an oxidative insult, wild-type p53 has been implicated as a central regulatory component of the mitochondrial permeability transition (mPT), triggering necrosis. This process is associated with cellular stabilization and translocation of p53 into the mitochondrial matrix. Here, we probe the mechanism by which p53 activates the key mPT regulator cyclophilin D (CypD). We explore the involvement of Trap1, an Hsp90-related mitochondrial matrix protein and a member of the mitochondrial unfolded protein response, and its ability to suppress mPT in a p53-dependent manner. Our study finds that catalytically active CypD causes strong aggregation of wild-type p53 protein (both full-length and isolated DNA-binding domain) into amyloid-type fibrils in vitro . The responsible CypD residues for this activity were mapped by NMR to the active site amino acids R55, F60, F113, and W121. The data also present a new proline isomerization assay for CypD by monitoring the aggregation of p53 as an indicator of CypD activity. Moreover, we find that the inhibition of Trap1 by the mitochondria-specific HSP90 ATPase antagonist Gamitrinib strongly sensitizes primary mouse embryonic fibroblasts to mPT and permeability transition pore opening in a p53- and CypD-dependent manner. We propose a mechanism by which the influx of unfolded p53 into the mitochondrial matrix in response to oxidative stress indirectly activates the normally inhibited CypD by displacing it from Trap1 complexes. This activates CypD's isomerase activity. Liberated CypD then isomerizes multiple proteins including p53 (causing p53 aggregation) and the structural components of the mPTP pore, inducing pore opening. This working model can now be tested in the future. Graphical Abstract: Highlights: Catalytically active CypD drives insoluble aggregation of p53 in vitro . Active CypD causes the p53DBD to aggregate into amyloid-like fibrils in vitro . Inhibition of Trap1 sensitizes mouse embryonic fibroblasts to mPT in a p53-dependent manner.